COTTON RESIDUE MANAGEMENT IN COTTON-GREEN GRAM CROPPINGSEQUENCE-AN ON FARM EVALUATION - G. RAKESH, G.ESWARA REDDY, Y. BHARATHI, M. VIJAYKUMAR, A. DINESH, N. SWAPNA, M. SAI CHARAN, G. NARENDAR, A. KRISHNA CHAITANYA, M. SRIDHAR and B.BALAJI NAIK (The Journal of Research, PJTSAU, 2026)
An on-farm trial was conducted during Summer 2025 at Ganeshwaram and Bodyathanda villages of Khammam, Telangana,to evaluate the effect of cotton residue management practices on the performance of greengram (MGG-351) under irrigatedconditions. The experiment was laid out in an On-Farm Research (OFR) design with three replications across farmer fields,comparing three treatments: T1– incorporation by rotavator, and FP – farmer’s practice (burning of stalks).Results revealed thatmechanical incorporation of residues using a incorporation by rotavator (T1) markedly improved growth and yield attributes such asplant height (58.6 cm), clusters per plant (7.0), and pods per cluster (7.0), compared to the farmer’s practice. The treatmentrecorded a 9.7% higher seed yield (1543 kg/ha) and enhanced haulm yield (3820 kg/ha) over burning (1393 and 3610 kg/ha,respectively). The economic analysis showed higher profitability with net returns of 91,367/ha and a B:C ratio of 2.92:1, surpassingthe farmer’s practice ( 75,967/ha; 2.53:1). Post-incorporation soil analysis indicated improvement in organic carbon and microbialactivity, confirming the beneficial effect of residue decomposition on soil health. The findings emphasize that mechanical incorporationof cotton residues using shredders is a sustainable, eco-friendly, and economically viable alternative to residue burning. Wideradoption through farmer training and access to shredding machinery can significantly enhance soil productivity and environmentalsustainability in cotton–greengram systems.